Modeling and Dynamic Contact Analysis of Spiral Bevel Gear based on Pro/E and Abaqus - Yu Zihao; Liu Zuoshi; Zhang Ping (Jixie chuandong, 2018)
The three-dimension coordinate equation of tooth surface of spiral bevel gear is obtained based on the forming principle of spiral bevel gear. According to the spiral bevel gear computational adjustment cards provided by the Gleason company,the three-dimensional model of spiral bevel gear pair is established by writing the MATLAB program to solve out the 3 D coordinates of discrete points on the tooth surface and using three dimensional modeling software. The contact analysis of bevel gear pair is completed by importing the 3 D model into the finite element software Abaqus to create the finite element model of spiral bevel gear. According to the analysis results,the change of the contact positive pressure of a pair of gear teeth in a complete meshing cycle is obtained,and the accuracy of the simulation results is verified by experiments which provides reference and technical support for the design,manufacture and optimization of spiral bevel gear.